2017
DOI: 10.1097/pcc.0000000000001000
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Binding Lectin Levels in Critically Ill Children With Severe Infections*

Abstract: Objective Low mannose-binding lectin (MBL) levels and haplotypes associated with low MBL production have been associated with infection and severe sepsis. We tested the hypothesis that MBL levels would be associated with severe infection in a large cohort of critically ill children. Design Prospective cohort study Setting Medical and Surgical Pediatric Intensive Care Units (PICUs), Boston Children’s Hospital Patients Children < 21 years of age admitted to the intensive care units from November 2009 to No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…A large cohort of hospitalized children with meningococcemia also did not have higher carriage of O alleles (49). In single center nested case-control PICU studies, we reported no differences in carriage of low-producing MBL2 variants in patients with severe infections (22) but others reported a 2-fold overall increase in carriage of the O allele with an increase in homozygotes (50). Although MBL2 haplotypes associated with deficiency appear to be a risk factor for a range of infections in neonates or other immune compromised patients, our study adds to the literature that carriage of low-producing MBL2 variants does not increase risk of severe viral infections (51).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…A large cohort of hospitalized children with meningococcemia also did not have higher carriage of O alleles (49). In single center nested case-control PICU studies, we reported no differences in carriage of low-producing MBL2 variants in patients with severe infections (22) but others reported a 2-fold overall increase in carriage of the O allele with an increase in homozygotes (50). Although MBL2 haplotypes associated with deficiency appear to be a risk factor for a range of infections in neonates or other immune compromised patients, our study adds to the literature that carriage of low-producing MBL2 variants does not increase risk of severe viral infections (51).…”
Section: Discussionmentioning
confidence: 66%
“…MBL deficiency is common, and may occur in 30% of the population depending on what MBL level cutoff is used for defining it; deficiency has been defined variably as <1,000, <500, <200, or <100 ng/mL (21). In critically ill patients, serum levels may be influenced by inflammation, diluted by fluid resuscitation, or raised via fresh frozen plasma transfusion, so genotype has been used as an inexact proxy to estimate pre-illness MBL deficiency (17, 22).…”
Section: Introductionmentioning
confidence: 99%
“…However in a recent study, MBL levels had no association with infection status at admission, or with progression from systemic inflammatory response syndrome to sepsis or septic shock in children admitted with severe or life-threatening illness 16 . It has also been shown that MBL deficiency is not associated with a susceptibility to influenza-related critical illness in children 17 .…”
Section: Introductionmentioning
confidence: 81%
“…Up to this day, a wide spectrum of other methods have been used for detection of MBL2 gene variants, including commercially available TaqMan assays [ 27 ], high-resolution melt analysis (HRMA) [ 28 ], reverse hybridization with membrane-immobilized sequence-specific oligonucleotide probes (reverse PCR-SSOP) [ 29 ], PCR with sequence-specific primers (SSP-PCR) [ 30 , 31 ], PCR and restriction-fragment length polymorphism (PCR-RFLP) analysis [ 32 ], an oligonucleotide ligation assay [ 33 , 34 ], a single-strand conformation polymorphism technique (PCR-SSCP) [ 35 ], the iPLEX assay on a MassArray system [ 36 ], Sanger sequencing [ 37 ], and pyrosequencing [ 38 ].…”
Section: Discussionmentioning
confidence: 99%